BENARKAH PENDIDIKAN MENENTUKAN TINGKAT PENGANGGURAN DI PROVINSI ACEH - Asrijal Asrijal; Syahril Syahril (Universitas Teuku Umar, 2022)
Aceh Province is one of the provinces that has the ninth highest open unemployment rate (TPT) out of 34 provinces throughout Indonesia with a ratio of 22.41%. This shows that the province of Aceh is currently still unable to overcome the problem of job vacancies for new graduates, resulting in an excess of manpower in the world economy. The purpose of this study was to analyze the level of education on the youth unemployment rate in Aceh Province through a statistical test approach. In this study using a descriptive quantitative type of research, this is intended to obtain an overview of how much influence the level of education has on youth unemployment in Aceh Province. The T-test in this study shows that the sig value of the education level has a significant and bound effect on the youth unemployment rate in Aceh Province. In addition, the coefficient of determination test is known that the effect that occurs on the level of education on the youth unemployment rate in Aceh Province is 89.1%. The results of the analysis reveal that the more graduates of the education level in an area, the greater the number of unemployed. The increase in new graduates, especially high school and undergraduate levels, will increase the competitiveness of human resources.